Modern Financial Tools’ Impact on Public Financial Management: The Case of Egypt - A.A.M.A. El-Saman (Финансы: теория и практика)
The purpose of this study is to examine the managerial impacts of applying modern public financial management (MPFM) tools in financial reform programs on the efficiency of public financial management (PFM) in developing countries, considering the case of the Egyptian reform program implemented during 2005–2015. Applying MPFM tools could improve the efficiency of PFM in developing countries if institutional factors are available to ensure their successful implementation in reform programs. The study adopted a descriptive-analytical method to describe the managerial impact of applying MPFM tools in the financial reform experiences in developing countries. It employed a case study approach on the Egyptian reform experiment to estimate the correlation between applying modern financial tools and the managerial efficiency of PFM assessed through three elements: operational efficiency, allocative efficiency, and financial discipline. The practical study used the IBM SPSS package and MS-Excel to process the data. The results found a positive correlation between the application of modern financial tools and the rate of improvement in the efficiency of PFM in the Egyptian reform program. The study developed a specific model for a deeper understanding of the impacts of MPFM tools on the efficiency of PFM. The model highlighted a strong positive correlation between the successful application of modern PFM tools and the efficiency of PFM and underscored that the availability of the required realtime financial information about governmental revenue and more control over public spending led to achieving financial discipline.